A Picnic on Mount Tom - Winiarski, Douglas Leo (Jonathan Edwards studies, 2012)
This a piece of John Walley’s Diary 1742-59, which we entitled A Picnic on Mount Tom. The transcript was kindly provided by Prof. Douglas Winiarski of the University of Richmond.